Thrombectomy in stroke of unknown onset, wake up stroke and late presentations: Australian experience from 2 comprehensive stroke centres. (January 2019) - Alsahli, Khalid; Cheung, Andrew K.; Wijesuriya, Nirupama; Cordato, Dennis; Zagami, Alessandro S.; Wenderoth, Jason D.; Chiu, Albert H.; Tay, Kevin; Cappelen-Smith, Cecilia
Highlights: Good "real world" outcomes are achievable in stroke patients treated with EVT > 6 h. Predictors of outcome include initial and 24 h clinical severity and large vessel occlusion site. Widespread access to perfusion imaging should improve patient selection and outcomes. Abstract: Two recent randomized controlled trials (RCTs) showed selected patients treated with endovascular thrombectomy (EVT) more than 6 h from acute ischemic stroke (AIS) onset had significant improvement in functional outcome at 90 days compared with standard care alone. Our aim is to determine the outcome and predictors of good outcome in AIS patients undergoing EVT with unknown-onset, or late presentation, stroke after 6 h from time last seen well, or witnessed stroke onset, at two Australian comprehensive stroke centres. A retrospective analysis of functional outcome and mortality at 90-days from a prospective cohort of 56 consecutive patients with unknown-onset, or late presentation, stroke with large vessel occlusion (LVO) in the anterior cerebral circulation undergoing EVT over a 15-month period (2016–2017). We evaluated factors which correlated with good functional outcome defined as a 90-day modified Rankin scale (mRS) 0–2. Recanalization times and symptomatic intracranial haemorrhage (sICH) rates were also examined. A good functional outcome was achieved in 35 patients (62%). Eight patients died (14%). Median time-to-recanalization was 7.6 h. SICH occurred in four patients (7%). Factors which predicted good 90-day functional outcome included baseline National Institutes of Health Stroke Scale (NIHSS) < 16, 24 h NIHSS < 10, baseline Alberta Stroke Program Early CT Score (ASPECTS) ≥ 8, pre-procedural CT perfusion imaging and LVO lesion location. This study shows good 'real world' outcomes, comparable to published RCTs, in patients with unknown-onset, or late presentation, stroke treated with EVT more than 6 h from stroke onset.